Views of Parents of Children With Neurodevelopmental Disabilities on Their Children's Social Media Use and Media Parenting - KILIÇ, FİDAN GÜNEŞ GÜRGÖR; Paftalı, Ayşe Tunç; Yıldız, Gizem (Taylor & Francis Ltd., 2025)
The aim of this study is to investigate the views of parents of children with neurodevelopmental disabilities regarding their children's use of social media, and their communication and approaches (media parenting) in teaching technologies to their children. A total of 319 parents participated in the study in which descriptive and relational survey models were used. According to the findings of the study, the participants' views on their children's social media use were negative regardless of all variables. On the other hand, the participants' media parenting levels were found to be high. No significant relationship was found between the participants' media parenting level and their views on social media use. The results showed that parents did not see social media as beneficial for their children in any circumstances, that they were very concerned about the use of social media, and that they exhibited a controlling and restrictive approach in media parenting.
Keywords: Media Parenting; Neurodevelopmental Disabilities; Parent View; Social Media; Special Needs